Doing Duoethnography: Addressing Essential Methodological Questions - Dawn Burleigh; Sarah Burm (International Journal of Qualitative Methods, 2022)
Duoethnography is a collaborative research methodology that invites researchers to serve as sites of inquiry. Through juxtaposition, the voices of each researcher are made explicit, working in tandem to untangle and disrupt meanings about a particular social phenomenon. We gravitate to duoethnography for its evocative power and the opportunity this methodology provides to engage in meaningful self-study in the presence of another. Yet, we grapple with methodological issues related to the unseen and unspoken enactments of the methodology. This article makes transparent the process of engaging in duoethnography by modeling its polyvocal dialogic nature while simultaneously addressing five essential questions about this collaborative research methodology. In this article, we retrace our collective journey engaging in duoethnography over the past 10 years, reflecting upon how our understanding and engagement with the methodology has shifted and expanded with each new inquiry. We make visible what is often invisible in the process of doing duoethnography, explicitly discussing our process for beginning and concluding a duoethnography, addressing what constitutes duoethnographic data, and the importance of cultivating a trustworthy and safe dialogical space. This article contributes to the existing methodological literature on duoethnography and further substantiates and generates transparency and teachability of this collaborative research approach.